Kinematic gait parameters for older adults with Parkinson's disease during street crossing simulation - Amaral-Felipe, Késia Maísa do [UNESP]; Yamada, Patrícia de Aguiar [UNESP]; Abreu, Daniela Cristina Carvalho de; Freire Júnior, Renato Campos; Stroppa-Marques, Ana Elisa Zuliani [UNESP]; Faganello-Navega, Flávia Roberta [UNESP] (Elsevier, 2020)
Safe street crossing is important for older adults' social inclusion. We assessed gait kinematic adaptation under different simulated street crossing conditions in older adults with Parkinson's disease (PD) and made comparisons with older adults without PD to understand how PD interferes in outdoor task performance, helping in the development of strategies to reduce road traffic accident risk. In 20 older adults without PD (control group – CG) and 20 with PD (GPD), we assessed usual gait (C1), gait during street crossing simulation (C2), and gait during reduced-time street crossing simulation (C3). Velocity, step length, and step, swing, stance, and double support time were analyzed. Spatiotemporal differences in gait between groups and conditions were analyzed. The GPD walked 16% slower in C1 and 12% slower in C2 and C3 than the CG. GPD also took 11% shorter steps in C1 and 9.5% shorter steps in C2. The double support time was 8.5% greater in C1. In intragroup comparisons, there were significant differences in all gait conditions. The CG showed increased velocity (C2 15% > C1; C3 13% > C2; C3 26% > C1), step length (C2 8% > C1; C3 5% > C2; C3 13% > C1), and swing time (C2 2% > C1; C3 3.7% > C2; C3 6% > C1), and decreased step time (C2 7.5% < C1; C3 8% < C2; C3 15% < C1), stance time (C2 1.3% < C1; C3 2.5% < C2; C3 3.6% < C1), and double support time (C2 6.3% < C1; C3 10.5% < C2; C3 16% < C1). GPD showed increased velocity (C2 19% > C1; C3 13.5% > C2; C3 29.7% > C1), step length, (C2 6% > C1; C3 7% > C2; C3 16% > C1), and swing time (C2 3% > C1; C3 3% > C2; C3 5.5% > C1) and decreased step time (C2 10.3% < C1; C3 7.7% < C2; C3 17% < C1), stance time (C2 1.7% < C1; C3 1.7% < C2; C3 3.4% < C1), and double support time (C2 7% < C1; C3 9.5% < C2; C3 16% < C1). Kinematic changes observed in the intergroup comparison show that participants with PD had lower velocity in all conditions. However, per the intragroup results, both participants with and without PD managed to significantly modify gait variables to attempt to cross the street in the given time. It is necessary to assess whether this increases fall risk by exposing them to road traffic accidents.
Keywords: Gait; Kinematics; Older adults; Parkinson's disease; Street crossing